Genome-Wide DNA Methylation Analysis Reveals Epigenetic Pattern of SH2B1 in Chinese Monozygotic Twins Discordant for Autism Spectrum Disorder - Liang, Shuang; Li, Zhenzhi; Wang, Yihan; Li, Xiaodan; Yang, Xiaolei; Zhan, Xiaolei; Huang, Yan; Gao, Zhaomin; Zhang, Min; Sun, Caihong; Zhang, Yan; Wu, Lijie (Frontiers in Neuroscience, 2019)
Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder. Aberrant DNA methylation has been observed in ASD but the mechanisms remain largely unknown. Here, we employed discordant monozygotic twins to investigate the contribution of DNA methylation to ASD etiology. Genome-wide DNA methylation analysis was performed using samples obtained from five pairs of ASD-discordant monozygotic twins, which revealed a total of 2397 differentially methylated genes. Further, such gene list was annotated with Kyoto Encyclopedia of Genes and Genomes and demonstrated predominant activation of neurotrophin signaling pathway in ASD-discordant monozygotic twins. The methylation of SH2B1 gene was further confirmed in the ASD-discordant, ASD-concordant monozygotic twins, and a set of 30 pairs of sporadic case-control by bisulfite-pyrosequencing. The results showed that there was a greater DNA methylation difference in ASD-discordant monozygotic twins than ASD-concordant monozygotic twins. Further, verification of the Chr.16:28856743 of SH2B1 showed significant differences in DNA methylation between case and control. These results suggest abnormal methylation of SH2B1 is associated with ASD etiology. Our data suggest that it might be worthwhile to further explore the functions of SH2B1 and related genes of neurotrophin signaling pathway in ASD.